Hospital-based maternal nutrition education for low-income families in managing child tuberculosis - Aini, Nurly Qurrota; Kustiyah, Lilik; Dewi, Mira (Universitas Gadjah Mada, 2024)
Purpose: Children with tuberculosis from low-income families are often referred to hospitals, yet research on hospital-based support is limited. This study evaluated a private hospital's tailored maternal nutrition education program and its impact on the food consumption and nutritional status of children with tuberculosis (24–59 months) from underprivileged families. Methods: This observational analytical study employed a one-group pretest-posttest research design. It was conducted from January to March 2024 at the Outpatient Department of Islami Mutiara Bunda Hospital, Brebes Regency. Secondary data from 2023 medical records of children with TB (24–59 months) from low-income families who received maternal nutrition education during the intensive phase were analyzed. A total of 59 samples were obtained through total sampling. Results: Among the children, 29 (49,2%) were boys and 30 (50,8%) were girls. By age, 33 children (55,9%) were 24–36 months, and 26 (44,1%) were 37–59 months. The percentage of energy deficiency before intervention in boys is higher than in girls (90% vs 74%). Almost all subjects experienced protein deficiency. After the intervention, there was an improvement in energy and protein adequacy. Both age groups experienced malnutrition at the age of 24-36 months, as much as 48%, and of 37-59 months, as much as 19%. After the intervention, the malnutrition group obtained good nutrition. Statistical tests (p<0,05) indicated maternal nutrition education significantly improved food consumption and nutritional status during the intensive phase. Conclusion: Tailored maternal nutrition education with two-way communication effectively enhances food consumption and nutritional status in children with TB from low-income families.